2014
DOI: 10.1080/10439463.2013.865737
|View full text |Cite
|
Sign up to set email alerts
|

Police management of mental health crisis situations in the community: status quo, current gaps and future directions

Abstract: This paper considers the application of principles widely used to conceptualise and address violent and aggressive behaviour in psychiatric settings and examines if and to what extent they may be applicable to the police resolution of community-based mental health crisis encounters. It suggests that police should distill the significant accumulated practical wisdom available within its ranks to inform the beginnings of an evidence-based approach regarding effective resolution of such incidents. These can then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…The first CIT was established in Memphis in 1988 as a direct response to the police shooting of a man suffering from serious mental ill health and sought to improve police officer identification of, and interaction with, vulnerable people experiencing mental health crises. Alternative models include mobile crisis teams where a mental health clinician is called as a secondary responder (Reuland and Margolis, 2003) and community service officers where individuals with social work experience complete a six week police training course before joining a police unit (de Tribolet-Hardy et al, 2014). Yet, despite widespread implementation of the CIT model across the United States there are inconsistent conclusions from evaluative studies about its efficacy (Fisher and Grudzinskas, 2010).…”
mentioning
confidence: 99%
“…The first CIT was established in Memphis in 1988 as a direct response to the police shooting of a man suffering from serious mental ill health and sought to improve police officer identification of, and interaction with, vulnerable people experiencing mental health crises. Alternative models include mobile crisis teams where a mental health clinician is called as a secondary responder (Reuland and Margolis, 2003) and community service officers where individuals with social work experience complete a six week police training course before joining a police unit (de Tribolet-Hardy et al, 2014). Yet, despite widespread implementation of the CIT model across the United States there are inconsistent conclusions from evaluative studies about its efficacy (Fisher and Grudzinskas, 2010).…”
mentioning
confidence: 99%
“…A police presence can expose service users to use of force as a consequence of unpredictable responses to officers who have a low tolerance to their instructions being challenged (Tribolet‐Hardy et al . ; White & Ready ). There is some evidence that the models of co‐responding are of benefit other than to police and the judicial system (Shapiro et al .…”
Section: Discussionmentioning
confidence: 99%
“…Service users have indicated that a coordinated response from both agencies has merits, but it would be preferable if police were not involved at all in crisis response (Boscarato et al 2014). A police presence can expose service users to use of force as a consequence of unpredictable responses to officers who have a low tolerance to their instructions being challenged (Tribolet-Hardy et al 2014;White & Ready 2009). There is some evidence that the models of co-responding are of benefit other than to police and the judicial system (Shapiro et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from issues surrounding job mobility, manifold other problems contribute to the intransigence of community blight that defy a quick fix, especially homelessness, drug addiction, and mental illness. The mentally ill inhabiting the area [41] require the expertise of trained professionals; [41] even police who are called to deal with troubled residents find this population to be especially challenging and fraught [42][43][44]. The move toward the deprivation of liberty of the mentally ill reveals the intractable nature of these problems and speaks to the extremity of the hurdles found in blighted communities.…”
Section: Entrenched Social Problemsmentioning
confidence: 99%